PRIMARY HEMOSTATIC SYSTEM CONDITION IN MUCOVISCIDOSIS IN CHILDREN - O. B. Gordeeva; V. V. Botvinyeva; O. I. Simonova; L. S. Namazova-Baranova; Y. V. Gorinova; E. L. Korolkova; M. A. Soloshenko; A. K. Gevorkyan (Педиатрическая фармакология, 2014)
The article presents results of a study of platelet hemostasis in children with mucoviscidosis. Motionless and viscous mucus  becomes infected with various pathogenic and opportunistic microbes in the setting of disturbed mucociliary clearance; when inflammation becomes chronic, endothelial dysfunction and platelet aggregation disorder may provoke development of bloodstream complications. Early diagnostics of pathologic changes in primary hemostasis is important for therapy and disease prognosis.